A Supramolecular Nanocomposite as a Near‐Infrared‐Transmitting Optical Filter for Security and Forensic Applications. Issue 46 (23rd October 2017) - Ghosh, Samrat; Cherumukkil, Sandeep; Suresh, Cherumuttathu H.; Ajayaghosh, Ayyappanpillai
Abstract: Visibly opaque but near‐infrared (NIR)‐transparent materials are an essential component for night‐vision photography, security imaging, and forensic applications. Herein, the development of a novel supramolecular black dye from a diketopyrrolopyrrole (DPP)‐based low‐molecular‐weight organogelator is described. In the solution state, the monomer of DPP–Amide exhibits a deep green color with a broad absorption in the visible region due to firm intramolecular charge transfer from the donor to the acceptor unit. Interestingly, due to the synergistic effect of H‐bonding and π‐stacking, DPP–Amide can form a black organogel in toluene with complete spectral coverage from 300 to 800 nm, and transmits beyond 850 nm. In the gel state, complete visible‐spectrum coverage is achieved due to the simultaneous formation of both H‐ and J‐type aggregates, which is confirmed via absorption studies. To create a free‐standing NIR‐transmitting elastomeric black filter, nanoscopic molecular aggregates of DPP–Amide (0.15 wt%) are embedded into a poly(dimethylsiloxane) matrix. This nanocomposite possesses high NIR transparency with good thermal and photostability for practical applications. Finally, the use of the developed material for NIR photography, security, and forensic‐related applications is demonstrated. Abstract : A π‐conjugated diketopyrrolopyrrole (DPP–Amide) forms a black supramolecular organogel with a broad spectral absorption from 300 to 800 nm, and transmits beyond 850 nm. A free‐standing near‐infrared‐filter lens fabricated by incorporating the nanoscopic molecular aggregates of the DPP–Amide into a poly(dimethylsiloxane) (PDMS) matrix is found to be useful for NIR photography, security, and forensic‐related applications.